Impact of AI-Driven Learning Management Systems on Institutional Efficiency and Student Engagement - Vaishali Rahate; Arvinder Kour Mehta; Shirisha Deshpande; Parag Jawarkar; Virendra Disawal; Pratiksha Sarge (Metallurgical and Materials Engineering, 2025)
AI-based Learning Management Systems (LMS) have transformed the educational industry by streamlining operational activities and boosting student engagement. The study investigates how the use of AI-based LMS can change certain educational parameters by looking at how they help to automate administrative processes, personalize learning, and enforce data-driven decision-making in academic settings. The research employs a mixed-methods approach, gathering quantitative data from faculty and students using structured surveys and qualitative insights through interviews with institutional administrators. AI for Learning Management: Streamlining Operations and Improving Outcomes AI-Powered LMS: Operational Efficiency The data-driven nature of AI for learning management systems allows organizations to optimize resource allocation and course delivery. In addition to that, it also leads to better student engagement and academic performance, through AI-based adaptive learning tools, smart feedback systems as well as predictive analytics. While the digital era has led to novel online learning frameworks, the emergence of AI-based LMS serves as a modernized educational approach, one that accommodates educational scalability through improved institutional productivity alongside enhanced student learning experiences, as we conclude from the analysis above. Yet future directions of research may include the investigating beyond the mere implications and the role of new AI technologies that may continue and push the education even further.